Prognosis of alcoholic peripheral neuropathy. - Hillbom, M (1984)
Ten male alcoholics aged 38-72 years with clear clinical and electroneurographical signs of peripheral neuropathy were re-examined three to five years later. Conduction velocities, latencies and nerve action potential amplitudes were measured from median, peroneal and sural nerves on both occasions and the results were compared with age-matched reference values from 80 healthy men. Seven of the alcoholics showed normal or nearly normal scores in electroneurographical and clinical examination and they had all managed to stop drinking alcohol. The results suggest that the prognosis of alcoholic peripheral neuropathy is good and independent of age provided that intake of alcohol is discontinued and other causes of neuropathy (malignancy, diabetes, nerve trauma) are carefully excluded.